Artificial intelligence in teaching technical English to nuclear engineering students - Zarochintseva, I. V.; Lupinogina, Yu. A.; Zakharova, L. V.; Kikinchuk, O. A. (Глобальная ядерная безопасность, 2024)
The paper considers the available artificial intelligence platforms used in the preparation of technical English assignments and the ways of motivation to learn a foreign language as the object of research. The processes of providing motivation for learning are chosen as the subject area. The objective of the research is to show the possibilities and spheres of AI use in foreign language teaching on the basis of analysing the information presented in the public domain about the existing ways of artificial intelligence application in foreign language teaching, as well as the conducted survey of nuclear engineering students. The methods used in the paper were theoretical analysis of scientific literature, analysis of periodicals, analysis of the practical use of AI in the work of teachers of the Department of Foreign Languages, as well as the data of the survey conducted among the students of technical specialities of VETI MEPhI. The main result of the research is the conclusion that the use of AI allows to diversify didactic material, provide motivation of students to master technical English and understand technological processes through the use of video content.